A thiocarbonyl-containing small molecule for optoelectronics. Issue 17 (7th February 2017) - Gendron, David; Maasoumi, Fatemeh; Armin, Ardalan; Pattison, Katherine; Burn, Paul L.; Meredith, Paul; Namdas, Ebinazar B.; Powell, Benjamin J.
Abstract : We report the synthesis, characterization, and device properties of a novel thiocarbonyl iso-DPP derivative, namely 1, 3, 4, 6-tetraphenylpyrrolo[3, 2- b ]pyrrole-2, 5(1 H, 4 H )-dithione. Abstract : We report the synthesis and characterization of a novel thiocarbonyl iso-DPP derivative, namely 1, 3, 4, 6-tetraphenylpyrrolo[3, 2- b ]pyrrole-2, 5(1 H, 4 H )-dithione. Even without solubilising alkyl chains, the small molecule could be processed from organic solvents such as dichloromethane, chloroform or dichlorobenzene, and it was found that the optical properties of neat thin films were strongly dependent on the solvent used. Field effect hole mobilities were of the order 10 −4 cm 2 V −1 s −1, with mobilities measured in a diode configuration solvent dependent and at least an order of magnitude lower. Importantly, blends of the iso-DPP derivative with PC70 BM, a typically used electron acceptor in bulk heterojunction solar cells, were found to possess hole mobilities of up to 10 −3 cm 2 V −1 s −1 in a diode configuration, which was an order of magnitude larger than the electron mobility. Finally, simple bulk heterojunction solar cells were fabricated with maximum power conversion efficiencies of 2.3%.